THE CORRELATIVE STUDY BETWEEN THE SPEAKING SKILL AND PSYCHOLOGICAL FACTORS OF THE STUDENTS - Nunung Anugrawati (Elite : English and Literature Journal, 2015)
The research aimed at identifying whether there was a correlation between students’ speaking skill and their psychological factors and what psychological factors had an existing correlation to the students’ speaking skill.The research used a Descriptive Study which involved two quantifiable variables and how closely they were related. The samples of the research consisted of 46 students and the data was obtained by using speaking test, checking reports, and questionnaires.The result of the research about relationship between students’ speaking skill and their psychological factors was determined by correlation coefficient in Pearson Product formula. The correlation coefficientwas 0.82 in the interval of 0.70 – 0.90, in which showing high correlation. In other words, there was a significant correlation between students’ speaking skill and their psychological factors. Intelligence, motivation and personality were the important factors of students’ psyche and they also represented psychological factors. Moreover, those factors had been proved one by one that they had an existing relationship to the students’ speaking skill through calculated data. Thecorrelation coefficients consisted of 0.57, 0.73, and 0.47 for each factor. It means that intelligence, motivation, and personality had existing correlation to the students’ speaking skill. Therefore, it was concluded that the higher psychological factors belonged to students, the better ability in speaking English would be achieved by themselves.